Pengaruh Motivasi dan Pengembangan Karier terhadap Disiplin Kerja yang Berimplikasi terhadap Kinerja Polisi Pada Direktorat Samapta Polda Jambi - Lingga, Ebon Anthony; Bukit, Pantun; Sudirman, Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this study is to obtain an overview of motivation, career development, work discipline and police performance at the Samapta Directorate of Jambi Police. To know and analyze the direct and indirect influence of motivation and career development on police work discipline at the Samapta Directorate of Jambi Police. To know and analyze the direct and indirect influence of motivation and career development on police performance at the Samapta Directorate of Jambi Police. To find out and analyze the effect of work discipline on police performance at the Samapta Directorate of Jambi Police. To know and analyze the influence of motivation and career development through work discipline on police performance The type of data obtained in this study uses quantitative data sourced from primary data obtained by conducting research and questionnaires, secondary data can be obtained by reading, learning and understanding through other media sourced from literature and library books or data from agencies related to the Researched. In this study, the object of research is the Directorate of Samapta Jambi Police. Motivation and Career Development simultaneously and partially have a significant effect on the discipline of personnel of the Samapta Directorate of Jambi Police. Motivation and Career Development simultaneously have a significant effect on the performance of personnel of the Samapta Directorate of Jambi Police. Motivation partially has a significant effect on the performance of personnel of the Samapta Directorate of Jambi Police. Meanwhile, partial career development has no significant effect on the performance of personnel of the Samapta Directorate of Jambi Police. Discipline partially has a significant effect on the performance of personnel of the Samapta Directorate of Jambi Police. Motivation and Career Development together have a significant effect on the discipline with performance. The suggestions put forward should be that the leader plays an active role in giving special attention accompanied by rewards so that in the process of work undertaken it gives good results.